2000
DOI: 10.1385/jmn:14:3:191
|View full text |Cite
|
Sign up to set email alerts
|

Reduced IL-2 But Elevated IL-4, IL-6, and IgE Serum Levels in Patients with Cerebral Infarction During the Acute Stage

Abstract: Cytokines in the central nervous system (CNS) may play an important role in functioning as intercellular signals that orchestrate the response to injury. Whether this is a cause or result of the brain disease process is uncertain. We investigated IFN-gamma, IL-2, IL-4, IL-6, and IgE in the sera of 38 patients with cerebral infarction during the acute stage and 10 normal controls using an originally devised sensitive sandwich enzyme-linked immunosorbent assay (ELISA). We found that serum levels of IL-2 derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
1
5

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 23 publications
3
60
1
5
Order By: Relevance
“…For example, in a recent study where animals were subjected to closed head injury, femoral fracture, and hemorrhagic shock, an increased inflammation, including elevated blood levels of IL-6 were reported compared to animals undergoing TBI alone (Probst et al, 2012). In clinical studies where secondary insults may be common, IL-6 has been reported to be an effective biomarker for brain injury severity and may be predictive for a delayed increase in intracranial pressure (Kim et al, 2000;Woiciechowsky et al, 2002;Hergenroeder et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a recent study where animals were subjected to closed head injury, femoral fracture, and hemorrhagic shock, an increased inflammation, including elevated blood levels of IL-6 were reported compared to animals undergoing TBI alone (Probst et al, 2012). In clinical studies where secondary insults may be common, IL-6 has been reported to be an effective biomarker for brain injury severity and may be predictive for a delayed increase in intracranial pressure (Kim et al, 2000;Woiciechowsky et al, 2002;Hergenroeder et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that IL-6, which is released by many hematogenous cells in response to injury and infection, plays a role in promoting T cell and B cell growth and is a predictive marker of stroke outcome [36]. Elevated levels of circulating IL-6 are found after stroke [37] and are correlated with infarct size [38] and poor outcome [39]. …”
Section: Discussionmentioning
confidence: 99%
“…In particular, there is little questions that the elevated production of IL-4 serves as an excellent marker of IS in vitro (Kim et al, 2000). However, the role of the IL-4 VNTR polymorphism in the risk for IS remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It was proposed that an increased responsiveness of the 2R allele to transcriptional activation might lead to the overexpression of IL-4 (Vandenbroeck et al, 1997). Furthermore, patients presented elevated IL-4 levels during the acute stage of cerebral infarction (Kim et al, 2000). The VNTR polymorphism of the IL-4 gene has been widely shown to be associated with a number of inflammatory diseases, including multiple sclerosis and idiopathic thrombocytopenic purpura as well as cerebrovascular disease (Vandenbroeck et al, 1997;Chen et al, 2007;Um and Kim, 2009).…”
Section: Introductionmentioning
confidence: 99%